Perbandingan Kemampuan Shooting Game Atlet Petanque Antar Kabupaten - Taajuddiin, Naufal Hafizh; Nurhidayat, Nurhidayat (Jurnal Porkes, 2022)
This study aims to examine the comparison of shooting game abilities between petanque athletes in Solo and Karanganyar district. This research was carried out for 2 days from March 19 to March 20 2022, the location of this research was carried out in the petanque raden mas said Karanganyar field and the petanque field in the city of Surakarta, the sample in the study was 20 athletes consisting of 10 petanque athletes in Karanganyar Regency and 10 Surakarta city athletes. The method used in this study is a survey research method with test instruments using shooting game station 1 to 5 ability tests. The results of the t test calculations can be seen with a significance value of 0.13 > 0.05, so it can be concluded that there is no significant difference in shooting game abilities between the city of Solo and Karanganyar district. If seen from the average value of the city of Solo 10.60 and the average value of Karanganyar district 13.80. Although there is no significant difference between the two research subjects, it can be seen that the shooting game ability of Karanganyar district is better because it has a higher average value of 13.80.